Identification of the Interactions Interference Between the PH and START Domain of CERT by Limonoid and HPA Inhibitors - Ghoula, Mariem; Le Marec, Axelle; Magnan, Christophe; Le Stunff, Hervé; Taboureau, Olivier (Frontiers in Molecular Biosciences, 2020)
The multi domain ceramide transfer protein (CERT) which contains the domains START and PH, is a protein that allows the transport of ceramide from the endoplasmic reticulum to the Golgi and so it plays a major role in sphingolipid metabolism. Recently, the crystal structure of the PH-START complex has been released, suggesting an inhibitory action of START to the binding of the PH domain to the Golgi apparatus and thus limiting the CERT activity. Our study presents a combination of docking and molecular dynamic simulations of N-(3-hydroxy-1-hydroxymethyl-3-phenylpropyl)alkanamides (HPA) analogs and limonoids compounds known to inhibit CERT. Through our computational study, we compared the binding affinity of 14 ligands at both domains (START and PH) and also at the START-PH interface, including several mutations known to play a role in the CERT’s activity. At the difference of HPA compounds, limonoids have a stronger binding affinity for the START-PH interface. Furthermore, 2 inhibitors (HPA-12 and isogedunin) were investigated through molecular dynamic (MD) simulations. 50 ns of molecular dynamic simulations have displayed the stability of isogedunin as well as keys residues in the binding of this molecule at the interface of the PH-START complex. Therefore, this study suggests a novel inhibitory mechanism of CERT for limonoid compounds involving the stabilization of the START-PH interface. This could help to develop new and potentially more selective inhibitors of this transporter, which is a potent target in cancer therapy.